Supervisor Role Modeling, Ethics-Related Organizational Policies, and Employee Ethical Intention: The Moderating Impact of Moral Ideology - Ruiz-Palomino, Pablo; Martinez-Cañas, Ricardo (2011)
The moral ideology of banking and insurance employees in Spain was examined along with supervisor role modeling and ethics-related policies and procedures for their association with ethical behavioral intent. In addition to main effects, we found evidence supporting that the person–situation interactionist perspective in supervisor role modeling had a stronger positive relationship with ethical intention among employees with relativist moral ideology. Also as hypothesized, formal ethical polices and procedures were positively related to ethical intention among those with universal beliefs, but the relationship was much weaker among relativists. Thus, firms wishing to optimally promote ethical attitudes and behavior must tailor their organization-based initiatives to the individual characteristics of their employees.
Keywords: Person–situation interactionist approach; supervisor’s role modeling; ethics-related policies and procedures; relativism/universalism; Ethical Behavior